Improving Cloud Streamed Gaming Quality using Latency Compensating GamePlay Enhancements (Pakistan Journal of Engineering, Technology and Science, 2024)
The arrival of Cloud Gaming (CG) has enabled video games to not require gamers to have a powerful machine with high-end processing capacity, and rather have the option to play them by streaming them while they get processed on a server, just like an internet video streaming site. Although, despite the ease of use that the service provides, its heavy reliance on an internet connection with high bandwidth and low latency hinders the service from being adopted more than it has so far, especially as higher latency results in poor game performance and decreased Quality of Experience (QoE). In this report, we discuss the current literature on the effects of delay in cloud gaming on players’ QoE, simulate variable delays that range from low to high randomly, and try to mitigate negative impacts on QoE caused by these delays by applying some proposed latency compensating enhancements on a game called “Shooting Star” which we developed for this experiment. We evaluated results after conducting an experiment by having the game played by crowd-workers, gathered their performance metricsand surveyed them about their feedback on their perceived QoE and responsiveness in different conditions such as no input delay, constant delays, and varying delays along with gameplay enhancement scenarios, the latter designed to mimic real-life Cloud Gaming conditions. The results of the study enable us to establish more accurately whether implementation of delay countering enhancements has a positive impact and are feasible to deliver depending on the worth of their reward. The study we conducted involved 140 total participants, and the results we analyzed indicated that the gameplay enhancements that we designed had a significant impact in mitigating the negative effects of delay on the players’ performance, and their perceived quality of experience and responsiveness.
Keywords: Cloud gaming; Streaming; Video games; Delay; Latency; Quality of Experience; Game performance